Effectiveness of brand presence on digital marketing by Positive Hub 360 - Mostafa, Chowdhury Fahim (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.